Current State of Type 1 Diabetes Immunotherapy: Incremental Advances, Huge Leaps, or More of the Same?. (18th July 2011) - Phillips, Brett; Trucco, Massimo; Giannoukakis, Nick
Abstract : Thus far, none of the preclinically successful and promising immunomodulatory agents for type 1 diabetes mellitus (T1DM) has conferred stable, long-term insulin independence to diabetic patients. The majority of these immunomodulators are humanised antibodies that target immune cells or cytokines. These as well as fusion proteins and inhibitor proteins all share varying adverse event occurrence and severity. Other approaches have included intact putative autoantigens or autoantigen peptides. Considerable logistical outlays have been deployed to develop and to translate humanised antibodies targeting immune cells, cytokines, and cytokine receptors to the clinic. Very recent phase III trials with the leading agent, a humanised anti-CD3 antibody, call into question whether further development of these biologics represents a step forward or more of the same. Combination therapies of one or more of these humanised antibodies are also being considered, and they face identical, if not more serious, impediments and safety issues. This paper will highlight the preclinical successes and the excitement generated by phase II trials while offering alternative possibilities and new translational avenues that can be explored given the very recent disappointment in leading agents in more advanced clinical trials.